Issues and Problems in Conducting Sensitive Research: A Case of HIV/AIDS in Nepal - Poudel, Ak Narayan; Newlands, David; Simkhada, Padam (Health Prospect, 2016)
The main aim of this paper is to explore the issues and problems along with possible solutions to conduct sensitive research, specifically research related to HIV/AIDS in Nepal. This paper is based on observation, information and experience obtained during research entitled, “The Economic Burden of HIV/AIDS upon Households in Nepal’ and literature reviews. There are many issues and problems in conducting sensitive research. Major issues and problems are- adherence to research ethics, use of research design and sampling, and recruitment of respondents in research. The paper concluded that research on sensitive topics like HIV/AIDS is very challenging and researchers need to strictly follow ethical procedures. Maintenance of anonymity and confidentiality are the key factors for encouraging participants to become involved in such sensitive research. Similarly, a mix of qualitative and quantitative methods help to understand the complex situations encountered during sensitive research. A non-probability sampling method is preferred over other methods of sampling in such research because there is often a problem of establishing a sampling frame in populations. Similarly, support from staff from government hospitals and NGOs is crucial if people living with HIV/AIDS are to be involved in the research. The issue of incentives is a highly discussed topic in sensitive research. But, it has been concluded that incentives especially in the monetary form should not be provided in order to avoid response bias and ethical conflicts.